The effects of stress on avian gene expression and microbiomes - Newhouse, Daniel J (East Carolina University, 2019)
Organisms must cope with stressors throughout their lifetime. Stressors are broad and come from both intrinsic and extrinsic sources. In this era of rapid global change, exposure to stressors will become more unpredictable and frequent. Thus, it is imperative we begin to understand how organisms respond to these stimuli. Birds are useful models to investigate responses to stress, as they are a diverse taxonomic group encompassing both well studied ecological and laboratory models. Here, I use several bird species and sources of stress to investigate how birds respond from a transcriptomic and microbiome perspective. The first two chapters investigate how infection and androgens impact gene expression of the avian immune system. In Chapter 1, I explore the avian immune transcriptomic response to West Nile virus, a common avian pathogen that has had devastating effects on birds since its emergence in North America. In Chapter 2, I test the Immunocompetence Handicap Hypothesis, which states that androgen-dependent sexually selected traits are costly to produce because androgens are simultaneously immunosuppressive. I used previously published transcriptome data and found support for the hypothesis. In Chapters 3 & 4, I turn my focus to early-life stress and white-throated sparrows (WTSPs). WTSPs exhibit two stable alternative parental care strategies, biparental care and female-biased parental care. In Chapter 3, I show that female-biased care induces a transcriptomic stress response in nestlings. In Chapter 4, I investigate the microbiome of WTSP nestlings and find no differences between individuals raised under the different parental care strategies. However, I do find some evidence of host genetic control of the microbiome. Overall, I have begun to explore how birds cope with various stressors, including infection, androgen induced immunosuppression, and developmental stress. Through primarily gene expression approaches, I uncover the molecular pathways affected by these stimuli. Each chapter will set the stage for future integrative work to explore organismal responses to their environment.
Keywords: genomics; transcriptomics; immune; Birds--Physiology; Ornithology; Animal behavior